Research on the Effect of Authenticity on Revisit Intention in Heritage Tourism - Zhou, Gefen; Chen, Wenkuan; Wu, Yuting (Frontiers in Psychology, 2022)
The authenticity of heritage tourism destinations is an important factor to attract tourists. Previous studies have shown that the relationship between authenticity and revisit intention. However, little attention has explored the impact mechanism of heritage tourism authenticity on revisit intention. Drawing on cognitive appraisal theory(CAT), we constructed a model of the mechanism underlying this relationship. The questionnaires were distributed in one world heritage site (The Dujiangyan irrigation system) in China, and 596 valid cases were collected. Using structural equation model, the results show that authenticity directly or indirectly effects tourists' revisit intention through memorable tourism experience (MTE) and place attachment. The research enriches the research on the existing literature on the relationship between authenticity and revisit intention, and provides a theoretical basis for promoting authenticity and revisit intention in heritage tourism.